Apparatus Professionalism and Public Service Ethics - Nurul Insani (Journal La Sociale, 2020)
To make changes in the organization and increase the professionalism of the apparatus it is important to redefine what the organization wants to achieve, build a payroll system that promotes the value of fairness and build organizational structures that allow for rapid decision-making processes. many factors can affect the professionalism of the apparatus, including the organizational culture that arises and crystallizes in bureaucratic traffic, organizational goals, organizational structure, work procedures in bureaucracy, incentive systems. Public service providers must study ethical norms that are universal because they can be used as guidelines for their behavior in providing services to the community.